A Typology for an Online Socrates Café. Issue 5 (May 2016) - Piro, Jody S.; Anderson, Gina
Background/Context: Increased polarization of viewpoints in the United States may have detrimental consequences for democratic pedagogy. The goals of civil society require a reliance on democratic values, and active participation is necessary for a strong civil society that demands the common good be deliberated in democratic ways. Discussion as pedagogy has been advanced for furthering democratic learning spaces in higher education with adults and in teacher education programs. Opportunities to participate in democratic discussions may also be created in online courses to prepare students who are literate in multiculturalism and an inclusive society. Engaging students in discussion that facilitates diverse perspectives and that challenges taken-for-granted assumptions is necessary. Purpose: This article explores the theoretical frameworks of a pedagogy of process called a Socrates Café, resulting in a typology for an online Socrates Café. This framework may assist instructors to create and sustain purposeful online discussion forums that engage students in deliberative discussion to develop democratic learning spaces and civil discourse. If democratic pedagogies are enhanced when people deliberate in online discussions by sharing their reasoning with each other, listening to competing points of view, considering new evidence, and treating one another as political equals, then the Socrates Café has much to offer as a pedagogical process. Research Design: Drawing on scholarship from key pedagogical and dispositional components, this analytical essay offers a typology that finds its theoretical roots in several areas, including: philosophical forum, discussion and dialogue, critical inquiry, habits of mind, intellectual traits, critical reflection, and civil discourse. Findings/Results: From both the pedagogical and dispositional components of the Socrates Café, we develop an integrative framework for guiding the creation and ongoing development of an online discussion. Our purpose in creating the framework was to determine those pedagogical and attitudinal dispositions that were foundational elements of the online Socrates Café: clarity of thinking and other habits of mind; attitudes of empathy, confidence, open mindedness and scholarliness; and questioning and dialogue. Conclusions/Recommendations: This essay concludes that the online Socrates Café is fraught with unavoidable contradictions resulting in a pedagogy of process that is negotiated and dynamic, but also purposeful and intentional. The integrative framework proposed in this work assists students to examine who they are as scholars, practitioners, and members of a democratic society. The inherent tensions between the competing values that situate the Socrates Café make it a complex pedagogy that invites students to encounter issues that surpass the self and connect them with larger societal problems, enhancing the potential for discussions that are purposeful and result in an expansion of perspectives. Supporting students as they negotiate these and other contradictions and paradoxes in a functional Socrates Café has immense potential for facilitating democratic spaces in pedagogy for civil discourse.